ICT, Clusters and Regional Cohesion: A Summary of Theoretical and Empirical Research - Carole Maignan; Dino Pinelli; Gianmarco I.P. Ottaviano (Fondazione Eni Enrico Mattei (FEEM), 2003)
The question of the spatial impacts of the Information and Communication Technology (ICT) has animated the intellectual and policy debate for a long time. At the beginning of the 1990s the rise of the Internet brought a new surge of debate: it was argued that the Internet would free the economy from the constraints of geography (Cairncross, 1997) bringing about a more even economic landscape. This contrasts sharply with the popular view of, for example, Silicon Valley, a congested area where world-class ICT and high-tech industries cluster together. In theory, geographical agglomeration of economic activities results as an equilibrium solution of a tension between centripetal and centrifugal forces. The paper discusses how the use of ICT may alter the balance between centripetal and centrifugal forces and therefore the final equilibrium solution. It shows that, from a theoretical point of view, there are many counterbalancing effects and not unique answer. The question is therefore down to empirical research. Available empirical evidences are then reported and discussed. Finally, the implications for European policies are drawn.
Keywords: O30; O40; 330; ICT; Clusters; Regional Cohesion; Informationstechnik; Agglomerationseffekt; Internet; Zentrum-Peripherie-Beziehungen; Produktionsstandort; Regionales Cluster; USA; EU-Staaten